Hearing Reaction Time Measurement Concentration Level Tool Integrated Android Smartphone - Muhamad Arif Indiarto; Syamsudduha Syahrorini (Procedia of Engineering and Life Science, 2021)
Performance in a job is very important because it will have an impact on the assessment and productivity of an employee, one of the indicators for evaluating high performance is related to concentration, execution speed and high productivity of the employee. Concentration is needed in working to prevent fatal accidents. In this study, it is possible to monitor measurement results via a smartphone, namely by using the Bluetooth HC-05 sensor as an integration to a smartphone. With 8 pushbutton, Arduino UNO microncontroller, Bluetooth HC-05, 16x2 LCD, and Buzzer. This tool works alternately when the push button Start is pressed, the power from the power supply will provide an electric current to the microncontroller, and continue to be connected to the Bluetooth HC-05, then by providing pushbuttons pressing input. Each pressing instruction on the pushbutton provides a different sound output, consisting of sound output, High, Mid, and Low. And continue on the LCD, and can display the results of the input that has been processed by the microcontroller. The output results are in the form of the amount of time displayed on the LCD, the sound from the buzzer, and from a series of work tools and the output results can be monitored via android smartphone. The results of this study are the accuracy of the tool in each variable low 99%, mid 90%, high 92%. The average tool ranges from 2.44. The error is low 7,4%, mid 7,4%, high 7,6%.